The Fashion of Syntax: Exploring the Function of Subordinate Clauses as Adjuncts in Vogue Magazine - Fasha Egi Mulyana, Putu Galuh; Putu Devi Maharani (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study examines the role of subordinate clauses as adjuncts in complex sentences from the "Living" category of Vogue Magazine articles published February 5–6, 2025. The study is motivated by the need to understand how these clauses contribute to the meaning and structure of sentences, particularly in written media, which often uses detailed and descriptive language. Using a descriptive qualitative method, the study analyzed 48 complex sentences from three articles. The subordinate clauses were classified according to their functions based on Aarts's (2001) theory. The analysis focused on adjuncts that provide additional information about time, reason, condition, and concession. The findings show that 21 subordinate clauses functioned as adjuncts. Adjuncts of condition were the most common among these, accounting for 38% of the data. They were followed by adjuncts of time (29%), concession (19%), and reason (14%). The results suggest that writers in Vogue frequently use conditional clauses to describe situations, possibilities, or hypothetical scenarios. The data were presented in formal tables, tree diagrams, and descriptive explanations. Using the theory of Aarts (2001) and Brown and Miller’s (1991) tree diagrams to provide structural analysis, this study contributes to a deeper understanding of how subordinate clauses, especially adjuncts, function to enrich written text. This study is expected to help students, teachers, and language enthusiasts explore syntactic elements in media texts.